The quality of recovery on discharge from hospital, a comparison between patients undergoing hip and knee replacement – a European study - Johansson Stark, Åsa; Charalambous, Andreas; Istomina, Natalja; Salanterä, Sanna; Sigurdardottir, Arun K; Sourtzi P., Panayota; Valkeapää K., Kirsi; Zabalegui, Adelaida; Bachrach-Lindström, Margareta (My University, 2016)
Aims and objectives: To describe and compare the quality of recovery on discharge from hospital among patients undergoing elective hip or knee replacement. The study will also attempt to identify any predicting factors. Background: Arthroplasty is commonly used for an increasing population of patients with osteoarthritis, and the recovery process starts directly after surgery. Today's shorter hospital stay may be a challenge for the patients during the early period of recovery. It is therefore important to identify factors associated with quality of recovery at discharge from hospital. Design: A descriptive, comparative study including 12 hospitals in 5 European countries; Cyprus, Finland, Greece, Iceland and Sweden. Methods: Consecutively included patients responded on: health-related quality of life, and emotions before surgery and at hospital discharge; quality of recovery, patient satisfaction and fulfilment of knowledge expectations. Related factors and associations were analysed separately for each kind of arthroplasty. In total, 865 patients were included (hip n = 413, knee n = 452). Results: In the dimension of pain, patients undergoing hip replacement had significantly better quality of recovery compared to those undergoing knee replacement. Both patient groups experienced negative emotions before surgery that were related to poorer quality of recovery. Fulfilment of knowledge expectations has a limited effect on quality of recovery. Greater satisfaction with care predicted better quality of recovery. Conclusions: Negative preoperative emotions were related to poorer quality of recovery. For both kinds of arthroplasty, greater satisfaction with care was associated with better quality of recovery. Relevance to clinical practice: The result emphasises the need to detect patients in need of support in their preparation and recovery process, taking into account the perspective of their emotional state.
Keywords: Fulfilment of knowledge expectations; Health-related quality of life; Hip replacement; Knee replacement; Preoperative emotional state; Quality of recovery; Satisfaction with care